2000
DOI: 10.1097/00005373-200011000-00011
|View full text |Cite
|
Sign up to set email alerts
|

C-Spine Injury Associated with Gunshot Wounds to the Head: Retrospective Study and Literature Review

Abstract: C-spine immobilization and diagnostic radiography are probably not necessary in patients with isolated GSWs to the head and may complicate and delay emergency airway management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 15 publications
0
20
0
1
Order By: Relevance
“…12 This is despite reports in literature that emphasizes the need to address life threatening injuries before the concern for immobilizing the neck as instability from the initial missile injury is rare. [13][14][15][16] For example, in patients with isolated GSW to the head, although there are reports that immobilization and diagnostic radiography is of minimal use, [17][18][19] Kaups et al, demonstrated that airway management was compromised by cervical immobilization as more intubation attempts occurred with cervical spine immobilization than without. 20 The emphasis of the mechanism of injury and its association with cervical spinal injuries would also be beneficial to the military where penetrating injury is the predominant mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…12 This is despite reports in literature that emphasizes the need to address life threatening injuries before the concern for immobilizing the neck as instability from the initial missile injury is rare. [13][14][15][16] For example, in patients with isolated GSW to the head, although there are reports that immobilization and diagnostic radiography is of minimal use, [17][18][19] Kaups et al, demonstrated that airway management was compromised by cervical immobilization as more intubation attempts occurred with cervical spine immobilization than without. 20 The emphasis of the mechanism of injury and its association with cervical spinal injuries would also be beneficial to the military where penetrating injury is the predominant mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in those studies that included all penetrating injuries (GSW and stab wounds), the majority indicated that most, if not all, of the spine injuries occurred in patients sustaining a GSW rather than stab wounds. 14,26,28,31 However, a subset analysis could not be performed on spinal injury in patients sustaining stab wounds because this group was not separated in most of the studies that reported both GSWs and stab wounds. Based on the studies in our analysis, the incidence of spinal injury in patients with isolated stab wounds is very low, and it is unlikely that PHSI in stab wound patients is of any benefit from a clinical and an economic standpoint.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to those of previous reports. 6,7 In cases of solitary gunshot wound to the head, there appears to be no need for radiographic clearance of the spine, and cervical spine protection is therefore not necessary. A high index of suspicion and careful radiographic evaluation of the spine is however recommended after gunshot wound to the face because asymptomatic injuries were common when significant spine injury was present.…”
Section: Discussionmentioning
confidence: 99%